Strengthening primary health care at district-level in Malawi - determining the coverage, costs and benefits of community-directed interventions - Peter Makaula; Mathias Funsanani; Kondwani Chidzammbuyo Mamba; Janelisa Musaya; Paul Bloch (BMC, 2019)
Abstract Background Community-Directed Interventions (CDI) is a participatory approach for delivery of essential healthcare services at community level. It is based on the values and principles of Primary Health Care (PHC). The CDI approach has been used to improve the delivery of services in areas that have previously applied Community-Directed Treatment with ivermectin (CDTi). Limited knowledge is available about its added value for strengthening PHC services in areas without experience in CDTi. This study aimed to assess how best to use the CDI approach to strengthen locally identified PHC services at district level. Methods This was a comparative intervention study carried out over a period of 12 months and involving four health centres and 16 villages assigned to 1) a conventional Essential Health Package (EHP)/PHC approach at health centre level or 2) an EHP/PHC/CDI approach at community level in addition to EHP/PHC at health centre level. Communities decided which intervention components to be included in the intervention. These were home management of malaria (HMM), long lasting insecticide treated nets (LLIN), vitamin A and treatment against schistosomiasis. The outcomes of the two strategies were compared quantitatively after the intervention was completed with regard to intervention component coverage and costs. Qualitative in-depth interviews with involved health professionals, implementers and beneficiaries were carried out to determine the benefits and challenges of applied intervention components. Results Implementation of the EHP/PHC/CDI approach at community level as an add-on to EHP/PHC services is feasible and acceptable to health professionals, implementers and beneficiaries. Statistically significant increases were observed in intervention components coverage for LLIN among children under 5 years of age and pregnant women. Increases were also observed for HMM, vitamin A among children under 5 years of age and treatment against schistosomiasis but these increases were not statistically significant. Implementation was more costly in EHP/PHC/CDI areas than in EHP/PHC areas. Highest costs were accrued at health centre level while transport was the most expensive cost driver. The study identified certain critical factors that need to be considered and adapted to local contexts for successful implementation. Conclusion The CDI approach is an effective means to increase accessibility of certain vital services at community level thereby strengthening delivery of EHP/PHC services. The approach can therefore complement regular EHP/PHC efforts. Trial registration The study was retrospectively registered with the Pan African Clinical Trial Registry TRN: PACTR201903883154921.